(untitled) (JS (JURNAL SEKOLAH), 2019)
Abstract: Improving Students’ Speaking Skills in Basic Competencies Understanding Technical Documents Using the Role Play Method in Class XI TPHP. The research subjects were 30th grade students of SMK Negeri Losida State. In cycle I held three meetings with an average learning outcome of 61.7. However, the results of the action in the first cycle have not been maximized because they have not reached the average of mastery learning â‰¥ 65. So to achieve the level of mastery learning is carried out improvements in teaching in the second cycle which ultimately resulted in an average value of 74.7. Based on observations of student learning activities obtained an increase by an average of 1.8 in the first cycle increased to 2.8 in the second cycle. Based on this it can be concluded that learning by using the role play method can improve student skills, especially English lessons in class XI TPHP students at SMK Negeri Losida. Keywords: understanding technical documents, methods, role play Abstrak: Meningkatkan Keterampilan Berbicara Siswa dalam Kompetensi Dasar Understanding Technical Documents Dengan Menggunakan Metode Role Play di Kelas XI TPHP. Subjek penelitian adalah siswa kelas XI SMK Negeri Losida berjumlah 30 orang. Pada siklus I dilaksanakan sebanyak tiga kali pertemuan dengan hasil belajar rata- rata 61,7. Namun hasil tindakan pada siklus I belum maksimal karena belum mencapai rata-rata ketuntasan belajar â‰¥ 65. Maka untuk mencapai tingkat ketuntasan belajar tersebut dilakukan perbaikan-perbaikan pengajaran pada siklus II yang pada akhirnya menghasilkan nilai rata- rata sebesar 84,6. Berdasarkan observasi aktivitas belajar siswa didapat peningkatan dengan rata- rata sebesar 1,8 pada siklus I meningkat menjadi 2,8 pada siklus II. Berdasarkan hal tersebut dapat diambil kesimpulan bahwa pembelajaran dengan menggunakan metode role play dapat meningkatkan keterampilan siswa khususnya pelajaran Bahasa Inggris pada siswa kelas XI TPHP SMK Negeri Losida. Kata kunci: understanding technical documents, metode, role play